Investigating neuropathological correlates of hyperactive and psychotic symptoms in dementia: a systematic review - Negro, Giulia; Rossi, Michele; Imbimbo, Camillo; Gatti, Alberto; Magi, Andrea; Appollonio, Ildebrando Marco; Costa, Alfredo; Poloni, Tino Emanuele (Frontiers in Dementia, 2025)
IntroductionBehavioral and Psychological Symptoms of Dementia (BPSD) are common neuropsychiatric manifestations that complicate the clinical course of dementia and impact caregiving. Among these, the Hyperactivity–Impulsivity–Irritiability–Disinhibition–Aggression–Agitation (HIDA) and Psychosis (P) domains are particularly challenging to manage. Despite their prevalence, their underlying mechanisms and neuropathological correlates, remain poorly understood. This systematic review aims to elucidate the neuropathological basis of the HIDA and psychosis domains, exploring whether distinct proteinopathies and neural circuit dysfunctions are associated with these symptoms.MethodsThe review follows PRISMA guidelines, with a systematic search conducted across MEDLINE, CENTRAL, and EMBASE databases. Inclusion criteria involved studies exploring the neuropathology of the HIDA and psychosis domains in individuals with dementia. Records were screened using PICO software, and data quality was assessed using the Newcastle-Ottawa Scale (NOS) and CARE guidelines. A narrative synthesis was conducted due to heterogeneity in the data.ResultsFrom 846 records identified, 37 studies met inclusion criteria. Of the 18,823 cases analyzed, the most common diagnoses were Alzheimer's Disease (83.44%), Dementia with Lewy Bodies (5.37%), and Frontotemporal Dementia (13.40%). HIDA-P symptoms were distributed across all clinical diagnoses, with agitation (14.00%), delusions (11.60%), disinhibition (7.61%), and hallucinations (6.83%) being the most frequently reported behaviors. The primary neuropathological diagnosis was Alzheimer's Disease Neuropathologic Change (ADNC), present predominantly in intermediate to severe forms. The neuropathological analysis revealed the co-occurrence of multiple proteinopathies, particularly TAUopathy, TDP-43 pathology, and Lewy-related pathology (LRP), with the latter, in association with ADNC, reported in 15 studies.DiscussionHIDA-P symptoms were linked with overlapping involvement of different neural circuits, particularly the amygdala and the broader limbic system. Evidence suggests that TAUopathy and multiple proteinopathies in key brain regions, such as amygdala, are central to the development of these symptoms. In contrast, the contribution of beta-amyloid and vascular damage appears marginal in the genesis of HIDA and psychotic symptoms. No behavioral symptom is pathognomonic of a specific proteinopathy; rather, the topography and severity of lesions plays a more decisive role than their single molecular composition.Systematic review registrationINPLASY2024100082.